2013
DOI: 10.1002/jor.22306
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of adult degenerative nucleus pulposus cells in a three‐dimensional microcarrier stirring culture system

Abstract: A major problem in reconstructing degenerative intervertebral discs is to obtain sufficient nucleus pulposus (NP) seeding cells with normal physiologic functions. The current study adopted a three-dimensional microcarrier culture system for massive cell expansion and evaluated the biological characteristics and physiological functions of the propagated adult degenerative NP cells. Isolated adult NP cells were cultured in either microcarrier stirring culturing system or traditional monolayer cultivation. The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Furthermore, we found that the number of MSCs captured on E7/PEG/pDA/Fe 3 O 4 -OA-PLGA under dynamic conditions was statistically significantly lower than the number of MSCs captured under static conditions ( Supplementary Table S1 ). Consistent with the preceding results, it is possible that shear forces affected early cell adhesion ( Ning et al, 2013 ), and such shear forces might, to some extent, also mimic the actual stress environment in vivo ( Zhang et al, 2010 ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, we found that the number of MSCs captured on E7/PEG/pDA/Fe 3 O 4 -OA-PLGA under dynamic conditions was statistically significantly lower than the number of MSCs captured under static conditions ( Supplementary Table S1 ). Consistent with the preceding results, it is possible that shear forces affected early cell adhesion ( Ning et al, 2013 ), and such shear forces might, to some extent, also mimic the actual stress environment in vivo ( Zhang et al, 2010 ).…”
Section: Resultssupporting
confidence: 80%
“…The total number of adherent cells on the surface of each microsphere decreased compared with that in static culture. Presumably, shear forces in the system may cause adhesion to take longer to achieve ( Ning et al, 2013 ). After modification with dopamine, the number of cells on the pDA/Fe 3 O 4 -OA-PLGA microspheres increased (versus the Fe 3 O 4 -OA-PLGA microspheres group).…”
Section: Resultsmentioning
confidence: 99%
“…At 1, 4, and 7 days, the cell/microcarrier constructs were rinsed with PBS, stained using Calcein-AM/PI Double Staining Kit, and then observed under confocal laser microscopy (Nikon Y-FL, Japan). Cell proliferation was also detected by MTT assay, as previously reported …”
Section: Experimental Sectionmentioning
confidence: 79%
“…Cell proliferation was also detected by MTT assay, as previously reported. 47 After 12 h of incubation, the cell/microcarrier constructs were fixed with 4% paraformaldehyde solution. The nucleus and cytoskeleton were fluorescently stained with Hoechst 33258 solution and TPITC Phalloidin solution.…”
Section: Methodsmentioning
confidence: 99%